2013
DOI: 10.1055/s-0032-1333425
|View full text |Cite
|
Sign up to set email alerts
|

The Value of 3.0-Tesla MRI in Diagnosing Scapholunate Ligament Injury

Abstract: Diagnosis of a complete scapholunate ligament (SLL) injury is most often largely based on history, clinical examination, and plain radiographs.1-3 Unfortunately, an unequivocal diagnosis cannot always be made because a rupture is partial or because a complete rupture has intact secondary scaphoid stabilizers (the scaphotrapeziotrapezoidal, scaphocapitate, and radioscaphocapitate ligaments). AbstractObjective To determine the sensitivity and specificity of 3.0-tesla (T) magnetic resonance imaging (MRI) and a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
(24 reference statements)
1
17
0
Order By: Relevance
“…Spaans et al studied a larger series of 38 wrists with a clinical suspicion of SL complex injury on 3 T MR and reported improved sensitivity rates between 70 and 81 % and a specificity of 100 % for SLIL tears. The results were comparable with the 3 T MRI studies with small series published by Hobby et al [39]. The previous comparative studies were performed on 1.5 T systems.…”
Section: Magnetic Resonance Imagingsupporting
confidence: 90%
“…Spaans et al studied a larger series of 38 wrists with a clinical suspicion of SL complex injury on 3 T MR and reported improved sensitivity rates between 70 and 81 % and a specificity of 100 % for SLIL tears. The results were comparable with the 3 T MRI studies with small series published by Hobby et al [39]. The previous comparative studies were performed on 1.5 T systems.…”
Section: Magnetic Resonance Imagingsupporting
confidence: 90%
“…26 Field strengths from 0.5 T to 1.5 T were included in the analysis, and higher sensitivity and accuracy was achieved whenever T2*-weighted 3D GRE sequences were used, probably because of the thinner slices and higher spatial resolution achievable with this technique. 26 Diagnostic performance studies published since then have generally shown further improved specificity, at or approaching 100% for both SLL and LTL tears at 3 T, 30,33,130,131 or at 1.5 T with intra-articular gadolinium (Tables 2 and 3). 32,35,36,132 The 1 study that had unusually low specificity was the only study that used indirect arthrography via an intravenous injection rather than an intra-articular injection.…”
Section: Diagnostic Performance Of Mr Imaging Scapholunate and Lunotrmentioning
confidence: 97%
“…106 In contrast, sensitivity has not significantly improved in more recent noncontrast MR imaging studies, even at 3 T, with sensitivities ranging from 41% to 89% for SLL tears and 22% to 82% for LTL tears, although these studies more commonly include partial tears, making direct comparison difficult ( Table 2). 30,32,33,36,72,130,131 One study that directly compared 1.5 T with 3 T found a statistically insignificant increase in sensitivity for both SLL and LTL tears. 33 Studies including MRA generally report higher sensitivity: 62% to 100% for SLL tears and 50% to 100% for LTL tears ( Table 3).…”
Section: Diagnostic Performance Of Mr Imaging Scapholunate and Lunotrmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25] Lowerresolution MRI scans, however, often do not provide enough information to diagnose carpal ligament lesions. [26][27][28] Depending on the surgeon's preference, diagnostic arthroscopy also can be used if the diagnosis remains in question.…”
Section: Relevant Anatomymentioning
confidence: 99%